ASSOCIATION BETWEEN HIGH RISK FOOT, RETINOPATHY AND HbA1c IN SAUDI DIABETIC POPULATION - Ahmed Aziz, Kamran Mahmood (Pakistan Journal of Physiology, 2010)
Background: One of the important complications of diabetes is diabetic-foot-ulcer, also reported in Saudi Arabia, like other countries. Similarly, the complications, like retinopathy and nephropathy are also occurring in diabetic patients of this region. Apart from the care and monitoring of these patients, it is important to find out association between these complications and their relation with common factors, like HbA1c levels. Such relation is not yet reported in literature. Objective: Therefore, this study was planned to find out association between neuropathy (leading to high risk foot) and retinopathy by the estimation of HbA1c levels in Saudi population. Methods: After exclusion of the cases of gestational diabetes and children with type-1 diabetes, 333 Patients having age 21 to 97 years were examined in the Diabetology Clinic of Diabetes Centre, Aseer Central Hospital, Abha. All patients were screened for neuropathy (High risk of the foot) and retinopathy (by Fundus Photography). HbA1c levels were determined, using standardised procedure. The obtained data was analysed statistically by SPSS-12 for Windows. Results: HbA1c levels of â‰¥10 have been found to be associated with neuropathy, high risk foot, and as well as non-proliferative and proliferative retinopathy. Pearson chi square test has demonstrated association between progressive retinopathy and development of high risk foot. Conclusion: The observed data indicate poor glycemic or diabetes control on the basis of higher HbA1c levels and strong association between high risk foot and the development of progressive retinopathy.